Kajian Literatur : Terapi Nonfarmakologis Terhadap Kualitas Tidur Pada Lansia - Agustina, Lisna (Jurnal Ayurveda Medistra, 2021)
Elderly is a term for individuals who have entered the period of late adulthood or old age. This period is the closing period for a person's life span, where there has been a gradual physical and psychological setback. One of the main aspects of improving health for the elderly is the maintenance of sleep to ensure the restoration of bodily functions to an optimal functional level and to complete tasks and enjoy a high quality of life. The purpose of this study was to determine the effectiveness of non-pharmacological therapies to improve sleep quality in the elderly who have sleep disorders both with and without illness. The methodology used is to search literature or study literature using electronic databased via the internet, namely google scholar and other electronic journals with the keywords elderly, sleep quality and nonpharmacological therapy. Literature review examines 10 related articles, found that nonpharmacological therapy significantly improves sleep quality in the elderly who have sleep disorders. Nonpharmacologic therapy is a complementary treatment option for the elderly with sleep disorders